Simulation studies of the interaction of laser radiation with additively manufactured foams. (1st April 2021) - Milovich, J L; Jones, O S; Berger, R L; Kemp, G E; Oakdale, J S; Biener, J; Belyaev, M A; Mariscal, D A; Langer, S; Sterne, P A; Sepke, S; Stadermann, M
Abstract: The interaction of laser radiation with foams of various porosities and low densities has been the subject of several numerical and experimental studies (Nicolaï et al 2012 Phys. Plasmas 19 113105; Perez et al 2014 Phys. Plasmas 21 023102). In all cases, the modeling of low-Z under-dense foams as uniform gases of equivalent average density using standard radiation-hydrodynamics codes has resulted in heat-front velocities that are considerably faster than those observed experimentally. It has been theoretically conjectured that this difference may be attributed to the breakdown of the foam's morphology, leading to a dynamics of filament expansion where the ion and electron energy partitions are significantly different from those calculated using the uniform gas model. We found that 3D computer simulations employing a disconnected representation of the foam's microstructure which allowed for the dynamics of foam element heating, expansion, and stagnation largely supported the theoretical picture. Simulations using this model for laser experiments on under-dense 2 mg cc −1 SiO2 aerogel foams (Mariscal et al 2021 Phys. Plasmas 28 013106) reproduced the experimental data fairly well. We used the validated model in simulations of low-density structured foam-like materials (produced via additive manufacturing) with a variety of morphologies. We found that the log-pile configurations were consistent with the analytical propagation model of Gus'kov et al (2011 Phys. Plasmas 18 103114). Further validation of the model was obtained by simulating experiments performed at the Jupiter Laser Facility using the log-pile and octet-truss foam morphologies. Simulations of the foam–laser interaction using a wave propagation code showed that the microstructure was able to enhance stimulated Brillouin scattering (SBS) by concentrating the light energy into density holes. In turn, this promotes laser filamentation, reducing SBS and bringing the predicted values closer to the experimental data.